2012
DOI: 10.1093/humrep/des020
|View full text |Cite
|
Sign up to set email alerts
|

Single embryo transfer with comprehensive chromosome screening results in improved ongoing pregnancy rates and decreased miscarriage rates

Abstract: BACKGROUNDSingle embryo transfer (SET) provides the most certain means to reduce the risk of multiple gestation. Regrettably, prospective trials of SET have demonstrated reductions in per-cycle delivery rates. A validated method of comprehensive chromosome screening (CCS) has the potential to optimize SET by transferring only euploid embryos. This retrospective study evaluates the efficacy of SET with CCS in an infertile population.METHODSOverall and age-controlled ongoing pregnancy rates (OPR) were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(143 citation statements)
references
References 30 publications
7
129
0
7
Order By: Relevance
“…2 Since 2008, there was emerging evidence regarding the use of array CGH in both translocation carriers and preimplantation aneuploidy screening. [3][4][5] Using aCGH, it could obtain information on all 24 chromosomes to detect aneuploidy, which is common in early human embryos, other than in translocated genetic material. 4 Recourse to WGA in aCGH allowed us to use a single blastomere for both diagnoses as the amplified products could also be used for PCR.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since 2008, there was emerging evidence regarding the use of array CGH in both translocation carriers and preimplantation aneuploidy screening. [3][4][5] Using aCGH, it could obtain information on all 24 chromosomes to detect aneuploidy, which is common in early human embryos, other than in translocated genetic material. 4 Recourse to WGA in aCGH allowed us to use a single blastomere for both diagnoses as the amplified products could also be used for PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding and expanded blastocysts underwent TE biopsy on day 5 or 6. The blastocyst quality was assessed immediately before TE biopsy, defined according to the criteria presented by Gardner and Schoolcraft (1999) [19]; only the blastocysts considered to be of a desirable quality (4,5,6, AB, BA, and BB) were subjected to biopsy. After TE biopsy, blastocysts were cultured in microdrops of a blastocyst medium with 15% SPS and a three-gas incubator until vitrification.…”
Section: Embryo Culturementioning
confidence: 99%
“…The high efficiency of PGS at the blastocyst stage has being reported as a key factor determining the growing clinical application of this strategy worldwide [2][3][4][5][6][7]. For blastocyst biopsy, laser-assisted drilling is used to create a zona opening on day 3 or day 5 of development.…”
Section: Introductionmentioning
confidence: 99%
“…Improved pregnancy rates and decreased miscarriage rates have been reported in SET cycles following CCS compared with SET using standard morphologic criteria [31,28]. Recent data from a randomized controlled trial even demonstrated that a SET of a chromosomally normal embryo has similar pregnancy rates to a DET of untested embryos [32].…”
Section: Introductionmentioning
confidence: 99%